Catalytic cracking of polycyclic aromatic hydrocarbons with hydrogen transfer reaction. (1st December 2015) - Shimada, Iori; Takizawa, Kouhei; Fukunaga, Hiroshi; Takahashi, Nobuhide; Takatsuka, Toru
Abstract: With the aim of enhancing oil refining processes based on fluid catalytic cracking (FCC), the catalytic cracking of polycyclic aromatic hydrocarbons (PAHs) was investigated using an FCC catalyst consisting of a rare earth ion exchanged USY zeolite. In these trials, model PAHs were dissolved in n -hexadecane and were fed into a fixed bed microactivity test reactor operating at 516 °C. Reaction product analysis indicated very little cracking of the 2-ring PAH over the FCC catalyst, while in contrast the 3-ring PAH was highly reactive, and was rapidly converted into monocyclic aromatic hydrocarbons, 2-ring PAHs and coke. Tests using FCC catalysts with different rare earth loadings revealed that the loading amount has little effect on the conversion of the 3-ring PAH. In addition, catalysts containing USY zeolites with comparable unit cell sizes, and thus having comparable hydrogen transfer activities, exhibited similar catalytic activities for 3-ring PAH conversion, even though they contained different amounts of the rare earth metal oxide. This result suggests that the hydrogen transfer reaction plays an important role in 3-ring PAH conversion and that the main effect of rare earth loading is to maintain the hydrogen transfer activity of the catalyst by stabilizing the USY zeolite against steam deactivation. In summary, this study successfully demonstrated a potential FCC process for converting PAHs into useful light fractions without the necessity of employing a pressurized hydrogen atmosphere.